Preparation method of honeycomb quartz product
By using quartz mineral preparing honeycomb quartz, the problem of dispersion, ultra -fine grinding, sintering sintering, and acid immersion process is used to solve the problem of unevenness and defects in the existing honeycomb ceramic preparation methods, and realize the high ratio surface area and structure. The intensity honeycomb quartz material improves catalytic efficiency and performance stability.
Patent Information
- Application Number
- CN202411433778.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
AI Technical Summary
The existing honeycomb ceramic preparation methods are prone to inhomogeneity and defects during the sintering process, which affects mechanical strength and stability; at the same time, the pore wall thickness and uniformity of honeycomb structures are difficult to accurately control, resulting in inconsistent performance.
The quartz ore or special mineral containing quartz is used to prepare honeycomb quartz. By disperse the sloppy, super fine grinding, sintering sintering, and acid immersion process to prepare a high -ratio surface area and a good honeycomb structure, it is prepared.
The high ratio and good structural strength of the honeycomb quartz material are realized, improved the catalytic efficiency and maintain the structural integrity and performance stability of the catalyst.
Smart Images

Figure CN119330739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral processing, more specifically, to a technical method for preparing honeycomb quartz by using quartz ore or special minerals containing quartz, and in particular to a method for preparing honeycomb quartz products. Background Art
[0002] Honeycomb ceramics are porous ceramic materials with a honeycomb structure, which are widely used in catalyst carriers, gas filters, exhaust purification devices and high-temperature gas purification. Its unique honeycomb structure provides a large specific surface area and excellent mass transfer performance, significantly improving the reaction and filtration efficiency. At the same time, honeycomb ceramics show good stability and mechanical strength in high temperature and corrosive environments, and are suitable for harsh industrial conditions.
[0003] At present, there are several methods for preparing honeycomb ceramics, including extrusion molding, mold injection molding and stacking molding. Honeycomb ceramics are obtained after drying and calcining the green body. There are some challenges and problems in the production and application of ceramics prepared by these methods. First, non-uniformity may occur during the sintering process, resulting in stress and defects inside the material, affecting its mechanical strength and stability. Secondly, during the extrusion or injection molding process, the pore wall thickness and uniformity of the honeycomb structure are difficult to accurately control, which may lead to inconsistent performance. In addition, although the high specific surface area of honeycomb ceramics improves the catalytic and filtration efficiency, it also increases the difficulty of clogging and cleaning. In order to overcome these problems, it is necessary to continuously optimize the material formulation, molding process and sintering parameters to improve the consistency and performance stability of the product. Summary of the invention
[0004] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solution: a method for preparing a honeycomb quartz product, which can utilize quartz ore or special minerals containing quartz to prepare a honeycomb quartz material with a high specific surface area and good properties, which can be used as a catalyst carrier to improve the application performance and use value of the quartz ore or special minerals containing quartz.
[0005] The present invention provides a method for preparing a honeycomb quartz product, comprising the following steps:
[0006] S1, preparing slurry;
[0007] S2, repeatedly superfine grinding the slurry;
[0008] S3, preparation of honeycomb quartz sintered samples;
[0009] S4, performing acid leaching, washing and drying treatment on the honeycomb quartz sintered sample to form honeycomb quartz.
[0010] Preferably, the S1 comprises:
[0011] S11, with d 95 Quartz ore with a particle size less than 74 μm or special minerals containing quartz are used as raw materials and added into a certain amount of water to form a first mixture;
[0012] S12, adding appropriate amounts of grinding aid, sintering aid and barrier agent to the first mixture, stirring and breaking up the mixture in a high-speed stirring disperser to form a slurry.
[0013] Preferably, the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: sintering aid: barrier agent is
[0014] =100:(100~800):(0.5~5):(40~60):(10~50);
[0015] Preferably, the grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the sintering aid includes sodium oxide and potassium oxide in a mass ratio of 1:1; the barrier is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier is 2 to 50 nm; the stirring and dispersing speed is 800-1200 rpm, and the stirring and dispersing time is 0.5h to 4h.
[0016] Preferably, S2 includes:
[0017] S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material;
[0018] S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
[0019] Preferably, the grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5 mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
[0020] Preferably, S3 includes:
[0021] S31, filtering the mixture slurry to form a filter cake;
[0022] S32, extruding the filter cake into a shape and isostatically pressing the filter cake into a honeycomb body;
[0023] S33, performing micro-sintering and calcining treatment on the honeycomb green body in a muffle furnace to form a honeycomb quartz sintered sample.
[0024] Preferably, the holding pressure during the filtration process is adjusted to 0.5-1.0 MPa; the isostatic pressing pressure is 10-30 MPa, and the holding time is 5-10 minutes; the temperature of the micro-sintering and calcining treatment is 700-1100°C, and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3h.
[0025] Preferably, S4 includes:
[0026] S41, placing the honeycomb quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agents and sintering aids;
[0027] S42, washing the acid-leached sample multiple times until the washing solution is in a neutral condition to obtain a neutral sample;
[0028] S43, drying the neutral sample to obtain the honeycomb quartz; wherein the honeycomb quartz has mesopores, and the size of the mesopores ranges from 2 to 50 nm.
[0029] Preferably, the mass ratio of the honeycomb quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.
[0030] Beneficial effects of the present invention:
[0031] (1) Innovatively use quartz ore or special minerals containing quartz as raw materials to prepare mesoporous quartz materials, and innovatively use micro-sintering technology to prepare mesoporous honeycomb quartz. Using honeycomb mesoporous quartz as a substrate can obtain a huge specific surface area, and the honeycomb structure can effectively reduce the mass transfer distance in the photocatalytic process, which can improve the catalytic efficiency. Honeycomb quartz also has a certain structural strength, which can keep the catalyst structurally intact and stable in performance during long-term use when used as a catalyst carrier.
[0032] (2) The processing method has a simple process flow, and honeycomb quartz can be obtained by breaking up the slurry, ultrafine grinding, micro-sintering and calcining, and acid leaching. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention provides a flow chart of the method for preparing the honeycomb quartz product.
[0034] Figure 2 The flowchart of step S1 provided by the present invention.
[0035] Figure 3 This is a flow chart of step S2 provided by the present invention.
[0036] Figure 4 The flowchart of step S3 provided by the present invention.
[0037] Figure 5 The flowchart of step S4 provided by the present invention. DETAILED DESCRIPTION
[0038] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0039] like Figure 1-5 As shown, this embodiment provides a method for preparing a honeycomb quartz product, comprising the following steps:
[0040] S1, preparing slurry;
[0041] As a preferred embodiment, the S1 includes:
[0042] S11, with d 95 Quartz ore with a particle size less than 74 μm or special minerals containing quartz are used as raw materials and added into a certain amount of water to form a first mixture;
[0043] S12, adding appropriate amounts of grinding aids, sintering aids and barrier agents to the first mixture, and stirring and breaking them up in a high-speed stirring disperser to form a slurry; the particle size in the slurry is the same as that of the raw material, because the stirring and breaking up step does not affect the particle size.
[0044] As a preferred embodiment, the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: sintering aid: barrier agent is
[0045] =100:(100~800):(0.5~5):(40~60):(10~50);
[0046] As a preferred embodiment, the grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the sintering aid includes sodium oxide and potassium oxide in a mass ratio of 1:1; the barrier agent is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier agent is 2 to 50 nm; the stirring and breaking speed is 800 to 1200 rpm, and the stirring and breaking time is 0.5h to 4h.
[0047] The amount of water and grinding aid in the ratio can improve the grinding efficiency, bringing advantages in energy consumption and product particle size. The amount of barrier agent affects the subsequent specific surface area. Adding more barrier agent will obtain a larger specific surface area, but it will also cause the sample strength to decrease. Therefore, as a more preferred embodiment, the grinding aid is sodium polyacrylate, the barrier agent is nano-calcium carbonate, and the particle size of the barrier agent is 5 to 10 nm; the mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: sintering aid: barrier agent = 100: (100 to 300): (1.5 to 2.5): (50 to 60): (30 to 50), the stirring and breaking speed is 1000 rpm, and the stirring and breaking time is 2h to 4h.
[0048] S2, repeatedly superfine grinding the slurry;
[0049] As a preferred embodiment, S2 includes:
[0050] S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material;
[0051] As a preferred embodiment, the grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5 mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
[0052] Among the dielectric materials, alumina is cheap, but it is easy to introduce impurity elements for pollution, while zirconium oxide is expensive and less polluting. The smaller the size, the higher the grinding efficiency, and the smaller the particle size obtained. The filling rate is related to the heat generation and grinding effect during the grinding process. Generally, the higher the filling rate, the better the grinding effect, but too high a filling rate will lead to a sharp increase in energy consumption, and the equipment will heat up seriously, causing the grinding aid to fail. Therefore, as a more preferred embodiment, the grinding medium material is zirconium oxide ceramic beads, the size of the zirconium oxide ceramic beads is Φ1mm~3mm, and the filling rate of the zirconium oxide ceramic beads in the grinding cavity is 70%~80%.
[0053] S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
[0054] S3, preparation of honeycomb quartz sintered samples;
[0055] As a preferred implementation, S3 includes:
[0056] S31, filtering the mixture slurry to form a filter cake;
[0057] S32, extruding the filter cake into a honeycomb body after isostatic pressing; the isostatic pressing pressure is 10-30 MPa, and the holding time is 5-10 minutes; the isostatic pressing technology is used in this embodiment, and the pressure is transmitted by liquid such as water or oil, which is mainly used for the preliminary pressing of powder materials. The technical effect is that the density and performance of the material can be significantly improved by uniformly applying high pressure, and it is suitable for the molding of parts with complex shapes;
[0058] S33, the honeycomb green body is subjected to micro-sintering and calcining treatment in a muffle furnace to form a honeycomb quartz sintered sample; in this embodiment, the constant temperature time is the time for keeping the temperature after the calcination reaches the specified temperature, and the heating process time is not included; the sample obtained by complete sintering is a ceramic, which is dense and will produce a molten phase during the sintering process, and the micro-sintering can be reflected by the surface area and the pore structure.
[0059] As a preferred embodiment, the holding pressure during the filtration process is adjusted to 0.5-1.0 MPa; the isostatic pressing pressure is 10-30 MPa, and the holding time is 5-10 minutes; the temperature of the micro-sintering and calcining treatment is 700-1100°C, and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3h.
[0060] If the calcination temperature is too high, the product will become dense and lose specific surface area. If the temperature is not high enough, the molten phase cannot be generated, resulting in sintering failure. The same is true for the calcination time. The calcination time is shorter at high temperature, while it takes a long time at low temperature. Therefore, as a more preferred embodiment, the pressure during the pressure filtration is adjusted to 0.8-1.0MPa; the pressure of the isostatic pressing of the billet is 25-30MPa, and the pressure holding time is 8-10 minutes; the temperature of the micro-sintering calcination treatment is 800-1000°C, and the constant temperature time of the micro-sintering calcination treatment is 1.5-3h.
[0061] S4, performing acid leaching, washing and drying treatment on the honeycomb quartz sintered sample to form honeycomb quartz;
[0062] As a preferred implementation, S4 includes:
[0063] S41, placing the honeycomb quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agents and sintering aids;
[0064] As a preferred embodiment, the mass ratio of the honeycomb quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.
[0065] In acid leaching, increasing the proportion of acid will increase the cost, and the amount of washing water will also increase during the acid cleaning process. However, the purification effect is better when the acid proportion is increased. Longer acid leaching time also has better effects, but the production efficiency is low. Therefore, as a more preferred embodiment, the mass ratio of the honeycomb quartz sintered sample to the hydrochloric acid is 100: (30-40), and the acid leaching time is 5-12 hours.
[0066] S42, washing the acid-leached sample multiple times until the washing solution is in a neutral condition to obtain a neutral sample;
[0067] S43, drying the neutral sample to obtain the honeycomb quartz; wherein the honeycomb quartz has mesopores, the size of the mesopores ranges from 2 to 50 nm, and the honeycomb quartz has a honeycomb structure as a whole, which increases the surface area and reduces the mass transfer distance during the reaction.
[0068] Application Examples
[0069] Example 1
[0070] This embodiment provides a method for preparing a honeycomb quartz material, comprising the following steps:
[0071] 1) With d 90 =68.35μm powder quartz ore is used as raw material, a certain amount of water, sodium polyacrylate grinding aid, sodium oxide and potassium oxide sintering aids and calcium carbonate barrier are added, and the mixture is dispersed in a high-speed stirring disperser for 1h.
[0072] Ratio: powdered quartz: water: grinding aid: sintering aid: barrier agent
[0073] =100:200:1.5:50:50
[0074] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ2mm zirconium oxide ceramic beads as grinding media with a filling rate of 70%. Grind the material repeatedly for 8 times. 90 =0.63μm.
[0075] 3) The slurry obtained in 2) was filtered under 1.0 MPa, extruded and then cold isostatically pressed at 25 MPa for 10 min, and then calcined in a muffle furnace at a calcination temperature of 900° C. for 1 h.
[0076] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0077] Ratio: powder quartz: hydrochloric acid = (100:40), acid leaching time 8h.
[0078] 5) After the acid leaching is completed, the filtration and washing are performed several times until the washing water is neutral, and then filtered and dried to obtain a honeycomb quartz material with a specific surface area of 70.43m 2 / g, and the volume proportion of mesopores is 76.96%.
[0079] Example 2
[0080] This embodiment provides a method for preparing a honeycomb quartz material, comprising the following steps:
[0081] 1) With d 90 =70.68μm quartz powder is used as raw material, and a certain amount of water, triethanolamine grinding aid, sodium oxide and potassium oxide sintering aids and zinc oxide barrier are added, and the mixture is dispersed in a high-speed stirring disperser for 1h.
[0082] Ratio: Quartz powder: Water: Grinding aid: Sintering aid: Barrier agent
[0083] =100:800:5:60:10
[0084] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ5mm alumina ceramic beads as grinding media with a filling rate of 80%. Grind the material repeatedly for 10 times. 90 =0.67μm.
[0085] 3) The slurry obtained in 2) was filtered and extruded at 0.5 MPa and then cold isostatically pressed at 10 MPa for 10 min, and then calcined in a muffle furnace at a calcination temperature of 900° C. for 3 h.
[0086] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0087] Ratio: powder quartz: hydrochloric acid = (100:50), acid leaching time 1h.
[0088] 5) After the acid leaching is completed, the filtration and washing are performed several times until the washing water is neutral, and then filtered and dried to obtain a honeycomb quartz material with a specific surface area of 56.18m 2 / g, and the mesopore volume is 56.65%.
[0089] Example 3
[0090] This embodiment provides a method for preparing a honeycomb quartz material, comprising the following steps:
[0091] 1) With d 90 =54.37μm quartz powder is used as raw material, and a certain amount of water, sodium hexametaphosphate, sodium oxide and potassium oxide sintering aids and zinc oxide barrier are added, and the mixture is dispersed in a high-speed stirring disperser for 1h.
[0092] Ratio: Quartz powder: Water: Grinding aid: Sintering aid: Barrier agent
[0093] =100:100:0.5:40:50
[0094] 2) Pump the slurry prepared in 1) into a vertical stirred mill for ultrafine grinding. Use Φ0.5mm alumina ceramic beads as grinding media with a filling rate of 65%. Grind the material repeatedly for 8 times. 90 =0.52μm.
[0095] 3) The slurry obtained in 2) was filtered and extruded at 1.0 MPa and then cold isostatically pressed at 30 MPa for 5 min. It was then calcined in a muffle furnace at a calcination temperature of 1100° C. for 0.5 h.
[0096] 4) The sample prepared in 3) was placed in a plastic storage tank, and hydrochloric acid was added for purification.
[0097] Ratio: powder quartz: hydrochloric acid = (100:20), acid leaching time 24h.
[0098] 5) After the acid leaching is completed, the filtration and washing are performed several times until the washing water is neutral, and then filtered and dried to obtain a honeycomb quartz material with a specific surface area of 60.29m 2 / g, and the mesopore volume is 65.11%.
[0099] The above embodiments grind quartz ore or special minerals containing quartz to submicron level, add barrier agents in the preparation stage of the green body, and use honeycomb molds, and innovatively use micro-sintering process to produce mesoporous channels. The mesoporous honeycomb structure provides a larger specific surface area and a higher porosity, which is beneficial to the dispersion of catalysts and the contact of reactants in subsequent use. The preparation of photocatalytic honeycomb quartz is achieved by utilizing the characteristics of the quartz sintering process. The high light transmittance of the quartz substrate of the present invention ensures that light energy can effectively penetrate the material and excite the catalyst, and has a higher photocatalytic efficiency than other photocatalytic products. Quartz has high mechanical strength and thermal stability. The honeycomb quartz substrate prepared by the present invention is a well-crystallized mesoporous quartz, in which the silicon dioxide component exists in the form of crystallized α-quartz, and its performance in acid and alkali resistance, high temperature resistance, corrosion resistance, etc. will be better than other amorphous ceramic materials, so that the catalyst maintains structural integrity and stable performance during long-term use.
[0100] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a honeycomb quartz product, characterized in that: The steps include: S1, preparing slurry; S2, repeatedly superfine grinding the slurry; S3, preparation of honeycomb quartz sintered samples; S4, performing acid leaching, washing and drying treatment on the honeycomb quartz sintered sample to form honeycomb quartz.
2. The method for preparing a honeycomb quartz product according to claim 1, characterized in that: The S1 includes: S11, with d 95 Quartz ore with a particle size less than 74 μm or special minerals containing quartz are used as raw materials and added into a certain amount of water to form a first mixture; S12, adding appropriate amounts of grinding aid, sintering aid and barrier agent to the first mixture, stirring and breaking up the mixture in a high-speed stirring disperser to form a slurry.
3. The method for preparing a honeycomb quartz product according to claim 2, characterized in that: The mass ratio of the quartz ore or special mineral containing quartz: water: grinding aid: sintering aid: barrier agent =100:(100~800):(0.5~5):(40~60):(10~50)。 4. The method for preparing a honeycomb quartz product according to claim 3, characterized in that: The grinding aid includes sodium polyacrylate, triethanolamine or sodium hexametaphosphate; the sintering aid includes sodium oxide and potassium oxide in a mass ratio of 1:1; the barrier is nano zinc oxide or nano calcium carbonate; the particle size range of the barrier is 2 to 50 nm; the stirring and dispersing speed is 800-1200 rpm, and the stirring and dispersing time is 0.5h-4h.
5. The method for preparing a honeycomb quartz product according to claim 4, characterized in that: The S2 includes: S21, pumping the slurry into a vertical stirred mill and adding grinding media to form a material; S22, repeatedly superfine grinding the material until d 90 <0.7μm to form a mixture slurry.
6. The method for preparing a honeycomb quartz product according to claim 5, characterized in that: The grinding media are alumina ceramic beads or zirconia ceramic beads; the size of the grinding media is Φ0.5-5 mm, and the filling rate of the grinding media in the grinding cavity is 65%-80%.
7. The method for preparing a honeycomb quartz product according to claim 6, characterized in that: The S3 includes: S31, filtering the mixture slurry to form a filter cake; S32, extruding the filter cake into a shape and isostatically pressing the filter cake into a honeycomb body; S33, performing micro-sintering and calcining treatment on the honeycomb green body in a muffle furnace to form a honeycomb quartz sintered sample.
8. The method for preparing a honeycomb quartz product according to claim 7, characterized in that: During the filtration process, the holding pressure is adjusted to 0.5-1.0 MPa; the isostatic pressing pressure is 10-30 MPa, and the holding time is 5-10 minutes; the temperature of the micro-sintering and calcining treatment is 700-1100°C, and the constant temperature time of the micro-sintering and calcining treatment is 0.5-3h.
9. The method for preparing a honeycomb quartz product according to claim 8, characterized in that: The S4 includes: S41, placing the honeycomb quartz sintered sample into a plastic storage tank, adding hydrochloric acid for acid leaching to obtain an acid-leached sample, wherein the acid leaching is used to remove excess barrier agents and sintering aids; S42, washing the acid-leached sample multiple times until the washing liquid is in a neutral condition to obtain a neutral sample; S43, drying the neutral sample to obtain the honeycomb quartz; wherein the honeycomb quartz has mesopores, and the size of the mesopores ranges from 2 to 50 nm.
10. The method for preparing a honeycomb quartz product according to claim 9, characterized in that: The mass ratio of the honeycomb quartz sintered sample to the hydrochloric acid is 100:(20-50), and the acid leaching time is 1-24 hours.